Unraveling Ross- classification of Anisembiidae (Embioptera) - Szumik, Claudia Adriana (2019)
The Southamerican family Anisembiidae appears as a monophyletic group in the first to the last published cladistic analyses of the Embioptera Order. However, half of the genera described by Edward S. Ross ? the specialist of order - appear as paraphyletic or polyphyletic groups (e.g. Bulbocerca, Dactylocerca, Pelorembia, Stenembia). The Anisembiidae, had - at the end of the 90 - a handful of genera (4-5) and around 40 species. Between 2001 and 2004, Ross published six compendia on Embioptera in the journal Occ. Paper of California Academy. One of them is a review of the family Anisembiidae, where he describes about 70 new species and 15 new genera (half of them monotypic), as well as groups like tribes and subfamilies. In this compendium is clear the conflict between the specialist?s point of view and the basic principle in systematics: achieve a stable classification; taxonomic groups should be supported by the evidence. As a result of this particular interpretation of the systematics, there are new genera grouping autapomorphic species of other well known genera and, geography as a criterion to define genera (e.g. the genus Mesembia exclusive for Cuba). Therefore, in this work we propose to analyze the whole group (around 110 species) and try to untangle Ross' classification in a phylogenetic context.grouping autapomorphic species of other well known genera and, geography as a criterion to define genera (e.g. the genus Mesembia exclusive for Cuba). Therefore, in this work we propose to analyze the whole group (around 110 species) and try to untangle Ross' classification in a phylogenetic context.